Dampak Peralatan Khusus terhadap Keterampilan Motorik dan Motivasi pada Pesilat Artistik Putra Junior - Donny Anhar Fahmi; Tubagus Herlambang; Agus Wiyanto; Danang Aji Setyawan; Fitri Yulianti (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Artistic gymnastics requires a high level of motor skills and sustained motivation, particularly among junior male athletes. The development of motor skills is closely linked to athletic performance, whilst motivation determines consistency in training and engagement in competition. This study investigated how an eight-session training programme using specialised artistic gymnastics apparatus (pommel horse, parallel bars, floor exercise, and horizontal bar) influenced the psychomotor development, motor skills, and motivation of junior male gymnasts. Materials and methods. A single-group pretest-posttest experimental design was used with 12 junior male gymnasts aged 15–16 years from Semarang, Central Java. Data were collected via validated motor skills assessments, a motivation questionnaire, and a psychomotor evaluation form. Data were analysed using a paired t-test with SPSS 23 to determine significant changes from the pre-test to the post-test. Results. The results of the study showed a significant increase in motivation scores, rising from a pre-test mean of 35.17 (SD = 5.01) to a post-test mean of 39.92 (SD = 4.94), t(11) = 4.23, p = 0.003. Artistic gymnastics performance improved from a pre-test mean of 36.08 (SD = 4.12) to a post-test mean of 40.67 (SD = 4.05), t(11) = 3.87, p = 0.011. Psychomotor skills also improved from a pre-test mean of 37.25 (SD = 2.70) to a post-test mean of 40.75 (SD = 2.68), t(11) = 4.11, p = 0.007. Conclusions. These findings confirm that structured training using specialised artistic gymnastics equipment effectively improves psychomotor performance and intrinsic motivation in junior male gymnasts. Further studies are recommended to use larger and more diverse samples to strengthen the generalisability of the findings.